A Case of Isolated Elevated Copper Levels during Pregnancy - LaToya R. Walker; Meghan Rattigan; Joseph Canterino (Hindawi Limited, 2011)
Introduction. Outside of Wilson's Disease, abnormal copper metabolism is a rare condition. In pregnancy, excess copper levels can be associated with intrauterine growth restriction, preeclampsia and neurological disease. Case Report. A 32 year old Gravida 4 para 2012 with an obstetrical history complicated by elevated copper levels presented for routine prenatal care. Her children had elevated copper levels at birth, with her firstborn child being diagnosed with autism and suffering three myocardial infarctions and being treated for elevated copper levels. During her prior pregnancies, she declined treatment for her elevated copper levels. During this pregnancy, she had declined chelation therapy and instead choose zinc therapy. She delivered a healthy infant with normal copper levels. Conclusion. Alterations in copper metabolism are rare, the consequences in pregnancy can be devastating. While isolated elevations of copper in pregnancy is exceedingly rare, it is treated the same as Wilson's disease. The goal is to prevent fetal growth restricting and neurological sequelae in the newborn and preeclampsia in the mother. Counseling, along with treatment options and timely delivery can greatly improve neonatal and maternal outcome.